The European Union and Multilateral Governance - Bruyninckx, Hans. author. aut Link
XIV, 285 p.
Keywords: An interdisciplinary approach to the study of the EU in UN human rights and environmental governance which addresses the legal and political science dimensions. With contributions from academics and policy-makers, this volume is a comprehensive analysis of how the challenges it faces impact on the EU's position in UN fora.